A comparative assessment of tree diversity, biomass and biomass carbon stock between a protected area and a sacred forest of Western Odisha, India. Issue 3 (3rd July 2019) - Pradhan, Antaryami; Ormsby, Alison A.; Behera, Niranjan
ABSTRACT: From September 2015 to January 2016, we studied the tree species diversity, biomass and biomass carbon stock of two different forests in Western Odisha: a wildlife sanctuary and a sacred forest. The wildlife sanctuary is entirely managed by the Forest Department, whereas the sacred forest is jointly managed by the local community and the Forest Department. Our results showed that the sacred forest had a greater species richness, density and diversity compared to the wildlife sanctuary. The density in different diameter classes showed that the sacred forest is regenerating with a good regeneration potential, but the wildlife sanctuary had a poor regeneration potential with lower numbers of saplings than adults. However, the biomass and carbon content of the wildlife sanctuary were higher than in the sacred forest. This may be due to the presence of a higher proportion of old trees in the wildlife sanctuary compared to the sacred forest. Biomass values can be used to emphasize the role of management in maintaining the carbon stock in forest ecosystems. Our results can be helpful in framing conservation strategies and action plans for forest patches in India and globally.